Angiotensin II Regulation of Proliferation, Differentiation, and Engraftment of Hematopoietic Stem Cells. Issue 3 (March 2016) - Kim, Seungbum; Zingler, Michael; Harrison, Jeffrey K.; Scott, Edward W.; Cogle, Christopher R.; Luo, Defang; Raizada, Mohan K.
Abstract : Emerging evidence indicates that differentiation and mobilization of hematopoietic cell are critical in the development and establishment of hypertension and hypertension-linked vascular pathophysiology. This, coupled with the intimate involvement of the hyperactive renin–angiotensin system in hypertension, led us to investigate the hypothesis that chronic angiotensin II (Ang II) infusion affects hematopoietic stem cell (HSC) regulation at the level of the bone marrow. Ang II infusion resulted in increases in hematopoietic stem/progenitor cells (83%) and long-term HSC (207%) in the bone marrow. Interestingly, increases of HSCs and long-term HSCs were more pronounced in the spleen (228% and 1117%, respectively). Furthermore, we observed higher expression of C–C chemokine receptor type 2 in these HSCs, indicating there was increased myeloid differentiation in Ang II–infused mice. This was associated with accumulation of C–C chemokine receptor type 2 + proinflammatory monocytes in the spleen. In contrast, decreased engraftment efficiency of GFP + HSC was observed after Ang II infusion. Time-lapse in vivo imaging and in vitro Ang II pretreatment demonstrated that Ang II induces untimely proliferation and differentiation of the donor HSC resulting in diminished HSC engraftment and bone marrow reconstitution. We conclude that (1) chronic Ang II infusion regulates HSC proliferation, mediated by angiotensin receptor type 1a, (2) Ang II accelerates HSC to myeloid differentiation resulting in accumulation of C–C chemokine receptor type 2 + HSCs and inflammatory monocytes in the spleen, and (3) Ang II impairs homing and reconstitution potentials of the donor HSCs. These observations highlight the important regulatory roles of Ang II on HSC proliferation, differentiation, and engraftment. Abstract : Supplemental Digital Content is available in the text.